Morphometric and molecular evidence for taxonomic recognition of a new subspecies of Armeria filicaulis (Plumbaginaceae) - Belén Gutiérrez Larena; Javier Fuertes Aguilar; Gonzalo Nieto Feliner (Anales del Jardín Botánico de Madrid)
A new subspecies of the Betic-Riffean species Armeria filicaulis is formally described –subsp. alfacarensis– from crystalline dolomitic sands NE of Granada (SE Spain). Its representatives exhibit a consistent morphological combination of characters on the inflorescence and flowers that support its taxonomic recognition. This is shown by means of a multivariate morphometric analysis. In one of the sites of the new taxon, where it is sympatric with A. villosa subsp. bernisii, nuclear ribosomal ITS sequences reveal gene flow between the two species, which is congruent with RAPD data and chloroplast trnL-F haplotypes. It is discussed that gene flow detected is not responsible for the origin of the new subspecies but a recent event. According to this, a differentiated biological entity related to other forms of A. filicaulis inhabiting dolomitic sands in eastern Andalusia, existed previously to gene flow events. The patterns detected (and inferred events) in A. filicaulis throughout its area suggest that the compilospecies model fits the evolution of this species as does that in A. villosa (as reported elsewhere) although not as closely.